Reinstatement of Aloe davyana var. subolifera (Asphodelaceae subfam. Alooideae), a distinctive variety of an endemic South African aloe - Smith, Gideon F.; Klopper, Ronell R.; Crouch, Neil R.; Figueiredo, Estrela (Phytotaxa, 2021)
Following the reinstatement of Aloe davyana Schönland (1905: 288) (Fig. 1A) as an accepted taxon at the rank of species, rather than at that of variety under A. greatheadii Schönland (1904: 121) (Smith et al. 2020), we here reinstate A. davyana var. subolifera Groenewald (1939: t. 732). Aloe davyana var. subolifera was accepted by all aloe researchers until it was placed in the synonymy of a broadened concept of A. greatheadii var. davyana (Schönl.) Glen & Hardy (1987: 490), a view with which we do not agree.